2008
DOI: 10.1007/s11433-008-0105-7
|View full text |Cite
|
Sign up to set email alerts
|

A probability density function of liftoff velocities in mixed-size wind sand flux

Abstract: With the discrete element method (DEM), employing the diameter distribution of natural sands sampled from the Tengger Desert, a mixed-size sand bed was produced and the particle-bed collision was simulated in the mixed-size wind sand movement. In the simulation, the shear wind velocity, particle diameter, incident velocity and incident angle of the impact sand particle were given the same values as the experimental results. After the particle-bed collision, we collected all the initial velocities of rising san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…In the present simulation, the particle angular velocity at the height of 1 mm can be considered as the lift-off angular velocity of the sand particle on the bed surface, and the probability density function of particle angular velocity at the height of 1 mm is consistent with the results of Zheng et al (2008).…”
Section: Probability Density Function Of Angular Velocity Of Particlessupporting
confidence: 74%
See 1 more Smart Citation
“…In the present simulation, the particle angular velocity at the height of 1 mm can be considered as the lift-off angular velocity of the sand particle on the bed surface, and the probability density function of particle angular velocity at the height of 1 mm is consistent with the results of Zheng et al (2008).…”
Section: Probability Density Function Of Angular Velocity Of Particlessupporting
confidence: 74%
“…With the discrete element method (DEM), Zheng et al (2008) found that the lift-off angular velocity of the sand particles lies between −1500 and 1100 rev/s, and the probability density function of the lift-off angular velocity distribution is a normal function. In the present simulation, the particle angular velocity at the height of 1 mm can be considered as the lift-off angular velocity of the sand particle on the bed surface, and the probability density function of particle angular velocity at the height of 1 mm is consistent with the results of Zheng et al (2008).…”
Section: Probability Density Function Of Angular Velocity Of Particlesmentioning
confidence: 99%
“…It is seen in Figure 4 that for * 0.5 u < m/s, the numerical results are very close to the value given by formula (17); while for * 0.6 u > m/s, the results are close to the value given by formula (16). Compared all the results in Figure 4, it is obvious that the sand transport rates calculated in the work agree well with those obtained from Bagnold's and Kawamura's empirical formulas in their respective effective regions, demonstrating that the model and the algorithm proposed in this work are correct and have a good efficiency in discussing the windblown sand movement.…”
Section: Calculation Methods and Validity Analysis Of The Saltation Mosupporting
confidence: 72%
“…These two empirical expressions are recognized to be very efficient [22][23][24] , and their respective effective regions are that the best accordance between the predictions of Kawamura's formula (17), in which K = 1.0, and the measurements of transport rate is only in the range of * 0.4 u < m/s; while for * 0.4 m/s 0.7 m/s, u < < Bagnold's formula (16) is more efficient; when the friction velocity increases continuously, all the predictions by formulas (16) and (17) are smaller than the experimental data.…”
Section: Calculation Methods and Validity Analysis Of The Saltation Momentioning
confidence: 99%
See 1 more Smart Citation